KETERAMPILAN KOMUNIKASI SISWA SETELAH DITERAPKAN STRATEGI ACTIVE KNOWLEDGE SHARING KETIKA PEMBELAJARAN DARING - Angeli Ramadina; Laily Rosdiana (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
When online learning students often then to less responsive especially when asking questions, it is necessary to have a strategy that can train student skills. The aims of this study was describe students written and oral communication skills during online learning by applying the active knowledge strategy of energy in living systems substances. This study type uses descriptive qualitative. Data from the observations were analyzed and then described. The results showed that most of students communication in the good category. The highest written communication skills in the indicator of organizing concept of 87,2 in the very good category. The lowest written communication skill is in the aspect of writing problem solving accurately and clearly at 71,4 in the good category. The highest students oral communication skill is the indicator of clarity/good articulation when speaking was 81,6 with the very good category. The lowest oral communication skill is the indicator of asking questions of 47,3 with a quite good category. Mind mapping is used to develop ideas, and creativity that students have. Learning uses the active knowledge sharing strategy provide many opportunities to communicate their opinions.